Channel Member’s Power and Dependence as a Determinant for Performance of a Distribution Channel within a South Asian Developing Country - Thusitha Weerasinghe Gunawardana (International Journal of Supply Chain Management, 2012)
Producers of industrial products designed for international markets use marketing intermediaries to execute an assortment of necessary functions to get the product to the final user. Managing distribution channel to fulfil the requirements of target market is a great challenge for these producers. Individuals and organizations that take part in distribution channel perform different roles in the distribution channel. Based on their dissimilarities in the distribution channel, the channel members will have different levels of power and dependence in relation to each other. Previous research shows that there is an inverse relationship between power and dependence in distribution channels in western countries. This inverse relationship may however not hold within national cultures characterized by a collectivistic social system. There is a lack of research on power dependence relationships within international distribution channels that combine producers of industrial products and middlemen located within countries with a strong collectivistic social system with channel intermediaries located in western countries. This study addresses the gap in the literature and proposes a study that is going to contributes to the literature by investigating power dependence relationships among channel members in an industrial distribution channel in a national culture characterized by a South Asian developing country. By using an exploratory research design, it is shown how channel members power and dependence is related to cooperation and trust among channel members and how cooperation and trust impact on the distribution chains performance. The study provides valuable insights that marketers in South Asian countries can utilize to develop more focused marketing strategies which may enable them to compete more effectively in the increasingly competitive markets.